2014
DOI: 10.14419/ijpr.v2i2.3361
|View full text |Cite
|
Sign up to set email alerts
|

Semi-empirical prediction of physical properties of (B3) TlP compound

Abstract: The principal goal of this work is the prediction only by means of some emperical formulas and two other physical quantities (the bond length and the bulk modulus calculated initially from first-principle calculations) of the refractive index, the exciton Bohr parameter, the electronic polarizability, the plasmon energy, the force constants, the optical band gap energy, the homopolar and heteropolar energies, the bonding-antibonding energy gap, the ionicity, the dielectric constant, and the optical susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Our value (15.58 eV) of ћωp for BSb compound is lower than the theoretical value 17.26 eV reported by Bioud et al [22]. Bulk modulus B is still used as a preliminary measure of the hardness of material but in order to confirm it, other properties must also be taken into account [23].There are several approaches usually used to determine the microhardness H of materials [24][25][26][27][28][29][30][31][32][33]. Chen et al [34] found that the hardness of polycrystalline materials correlated with the product of the squared Pugh's modulus ratio and the shear modulus, while Attard [35] found a linear function between the covalent charge and the reduced microhardness for several III-V semiconducting materials.…”
Section: Theory Results and Discussioncontrasting
confidence: 58%
“…Our value (15.58 eV) of ћωp for BSb compound is lower than the theoretical value 17.26 eV reported by Bioud et al [22]. Bulk modulus B is still used as a preliminary measure of the hardness of material but in order to confirm it, other properties must also be taken into account [23].There are several approaches usually used to determine the microhardness H of materials [24][25][26][27][28][29][30][31][32][33]. Chen et al [34] found that the hardness of polycrystalline materials correlated with the product of the squared Pugh's modulus ratio and the shear modulus, while Attard [35] found a linear function between the covalent charge and the reduced microhardness for several III-V semiconducting materials.…”
Section: Theory Results and Discussioncontrasting
confidence: 58%
“…To the best of our knowledge, this material and other materials of this family (TlAs and TlSb) have not been synthesized yet, and there are only a few theoretical works [1][2][3][4][5][6][7][8][9] on this materials are available. Using plane-wave pseudopotential (PW-PP) approach in the framework of density-functional theory (DFT) within the local density approximation (LDA) and generalized gradient approximation (GGA), the phase transition, the structural parameters, the band structures, the total electronic density of states (DOS) and other thermophysical properties of cubic zincblende TlP and TlAs compounds have been studied by Ciftci et al [2].…”
Section: Introductionmentioning
confidence: 99%